2008
DOI: 10.1016/s0924-9338(08)70055-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of Turkish patients with depression in Ankara and in Berlin

Abstract: QOL of Turkish patients with depression in Berlin appears lower than that of similar patients in Ankara. Different factors may influence QOL of Turkish patients with depression living in the place of origin and having emigrated to Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(17 reference statements)
1
8
0
3
Order By: Relevance
“…Although a feeling of emptiness alone is not a substitute for a clinical diagnosis of depression, the finding that Turks of both generations and across all age groups had higher risks of feelings of emptiness may indicate a significantly higher risk for depression (Klonsky, 2008;Whelan et al, 2008), and is consistent with earlier findings suggesting a vulnerability to psychological pathology (Haasen et al, 2000;Iren Akbiyik et al, 2008). Although previous studies have suggested a curvilinear relationship between age and well-being, no clear agerelated trend was found for the emptiness variable in this study (Blanchflower and Oswald, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although a feeling of emptiness alone is not a substitute for a clinical diagnosis of depression, the finding that Turks of both generations and across all age groups had higher risks of feelings of emptiness may indicate a significantly higher risk for depression (Klonsky, 2008;Whelan et al, 2008), and is consistent with earlier findings suggesting a vulnerability to psychological pathology (Haasen et al, 2000;Iren Akbiyik et al, 2008). Although previous studies have suggested a curvilinear relationship between age and well-being, no clear agerelated trend was found for the emptiness variable in this study (Blanchflower and Oswald, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Rather, Turkish immigrants have been reported as having higher morbidity rates especially at older ages (Lechner and Mielck, 1998;Marmor, 1988), and as having more exposure to occupational health risks (Razum et al, 2005). Turkish immigrants in Germany may also be more vulnerable to depression (Iren Akbiyik et al, 2008;Suzuki, 1981), and have a higher risk of developing psychiatric pathologies like schizophrenia (Haasen et al, 2000). Although the causes remain incompletely understood, past research suggests that lower educational and SES status (Constant and Massey, 2005;Ochs, 2006;van Doorslauer et al, 2006;Worbs, 2003), cultural barriers (Keller and Baune, 2005;Marmor, 1988), the stress associated with migration (Kirkcaldy et al, 2006;Razum et al, 2004), and a lack of health knowledge (David and Borde, 2000;Pette et al, 2004) are likely contributors to these health disparities.…”
mentioning
confidence: 99%
“…We therefore believe that patients' perception of marital adjustment dictates, to a large extent, the QOL perceived by them, thereby making it imperative that provision of mental health care should start to be based on needs of care assessments, instead of following certain protocols or prescribed guidelines, and research in this field is necessary to better plan and organize mental health services. As evidence accumulates that marital status may play a significant role in mental health (Afifi et al, 2006;Akbiyik et al, 2008), it becomes extremely important to develop differing forms of care and other forms of help for informal carers because most of the burden of caring for people with severe mental illness in less-developed countries relies mainly on spouses.…”
Section: Discussionmentioning
confidence: 99%
“…From the earliest studies that detected greater marital discord in marriages with a patient with SC (Weintraub, 1987) to current studies that have observed high rates of broken marriages and marital maladjustment in SC (Thara and Srinivasan, 1997a), the consensus is that marital adjustment dictates the course and the outcome of SC (Jablensky, 2009). Similarly, recurrent depressive disorders (RDDs) have been observed to have significant marital maladjustment (Akbiyik et al, 2008;Weintraub, 1987;Wells et al, 1989), with both outcome (Denton et al, 2010) and severity of depressive symptoms linked to severity of marital maladjustment (Heene et al, 2007;Waring and Patton, 1984). However, a study from similar settings in India observed poor marital adjustment in depressive disorders but found no evidence of its link to psychosocial functioning or QOL (Subodh et al, 2008).…”
mentioning
confidence: 99%
“…There is broad consensus on the view that migration constitutes a stress factor for migrants as well as for those left behind [11] but there is no agreement in the literature whether migrants in general are at a higher risk for mental, specifically affective disorders or suicidal behavior [2,12,40,55]. In this context, Bhugra [9] pointed to the importance of the interaction of individual, group and societal factors in the genesis of depression.…”
Section: Discussionmentioning
confidence: 99%